Power allocation and range performance considerations for a dual-frequency EBPSK/MPPSK system. Issue 12 (2nd December 2017) - Yao, Yu; Wu, Lenan; Zhao, Junhui
ABSTRACT: Extended binary phase shift keying/M-ary position phase shift keying (EBPSK/MPPSK)-MODEM provides radar and communication functions on a single hardware platform with a single waveform. However, its range estimation accuracy is worse than continuous-wave (CW) radar because of the imbalance of power in two carrier frequencies. In this article, the power allocation method for dual-frequency EBPSK/MPPSK modulated systems is presented. The power of two signal transmitters is adequately allocated to ensure that the power in two carrier frequencies is equal. The power allocation ratios for two types of modulation systems are obtained. Moreover, considerations regarding the range of operation of the dual-frequency system are analysed. In addition to theoretical considerations, computer simulations are provided to illustrate the performance.